STRATEGY OF CORPORATE SOCIAL RESPONSIBILITY (CSR) OF BANK RAKYAT INDONESIA (BRI) IN IMPROVING RELATIONS WITH THE REGIONAL DEVELOPMENT PLANNING AGENCY (BAPPEDA) OF MALANG REGENCY - Baru, Yosephina Anchieta; Arvianti, Eri Yusnita; Sasmito, Cahyo (MAP Observer: Jurnal Penelitian Administrasi Publik, 2024)
Through the strategic CSR policy contained in Law no. 47 of 2017 is a strategic step by the government so that companies have social responsibility towards the communities around the company’s operational areas. CSR itself (Corporate Social Responsibility) or what is also known as corporate social responsibility has been frequently used by various companies in Indonesia since the 1990s. One of the many limited liability companies whose operational area is in Malang Regency is Bank Bri Malang Kawi Branch. Based on the mandate of this law, BRI Bank should contribute to implementing social responsibility in Malang Regency. However, the sustainability of this CSR program is very dependent on the creation of mutually beneficial relationships between stakeholders. Using a Quantitative and Qualitative approach (Mix Methods), studied BRI’s CSR Strategy in Improving Relations with BAPPEDA Malang Regency and found three indicators according to Maruf (2019), namely Strategy Formulation (Strategy Formulation), Strategy Implementation (Implemented Strategy) and Strategy Evaluation and Supervision. The research results show that BRI’s CSR strategy is to improve relations with BAPPEDA Malang Regency. In this case, the collaboration between BRI Bank Kawi Malang Branch and the Malang Regency Government is limited to reporting CSR programs.